Macroeconomics. - Dornbusch, Rudiger; Fischer, Stanley (New Delhi McGraw-Hill Education, 1994)
A major revision of a textbook on intermediate macroeconomics, a new emphasis on long run growth is now added to the book's strengths and even more international material - particularly international policy examples - is featured. "Macroeconomics", by two internationally known economists, offers a balance of theory, economic policy and real-world data. It covers open-economy (international) aspects of macroeconomics, as well as micro-foundations of macroeconomic theory, and it presents even-handed views of major schools of thought in macroeconomics. In this new edition, the streamlined presentation eliminates extraneous material, and consolidates material more effectively. Current policy issues of the 1990s are highlighted and up-to-date economic data is used throughout.